PELAKSANAAN PEMBERIAN KREDIT DENGAN JAMINAN HAK TANGGUNGAN PADA PT. PERMATA BANK Tbk CABANG PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 4 TAHUN 1996 TENTANG HAK TANGGUNGAN ATAS TANAH BESERTA BENDA-BENDA YANG BERKAITAN DENGAN TANAH - Tama, Putra Davi; Bachtiar, Maryati; ', Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Lending activities have become a regular thing done by people in this age of globalization. Where to supplement their daily needs and build a national economy. Various financial institutions are banks and other financial institutions, non-bank can lend money by way of a credit system. And to avoid the risk of the bank makes credit system by using collateral. PT. Bank Permata Tbk Pekanbaru Branch is one of the conventional banks in the city of Pekanbaru which help people to do the credit system by using collateral, one of its collateral mortgage rights.Based on the above, the problems which the author adopted is about the implementation of the provision of credit to guarantee the mortgage rights in PT. Bank Permata Tbk Branch Pekanbaru, implementation constraints loans with collateral security rights in PT. Permata Bank Branch Pekanbaru and settlement in the event of default on the implementation of the provision of the credit.This type of research the authors classified into types of observational research studies in a way that is direct research survey conducted at the site of research that is how the implementation of the provision of credit to guarantee the mortgage rights in PT. Bank Permata Tbk Branch Pekanbaru. The location of this study conducted at the Branch Office of PT. Bank Permata Tbk Branch Pekanbaru located on Sudirman street Number 136-138 Pekanbaru with a population of customers who make a credit agreement with the guarantee of the right of dependents that as many as 79 people with a sample of 20 people. Besides distributing questionnaires, observation and literature study, the authors also interviewed the Credit Administration PT. Bank Permata Tbk Branch Pekanbaru to obtain document.Implementation of credit to guarantee the mortgage rights in PT. Bank Permata Tbk Branch Pekanbaru is in written form by filling out a credit application form and on the implementation of the provision of credit, difficulties. Namely from the incomplete requirements so that the obstruction to do credit disbursement and also guarantee does not cover the loan so that the loan must be insured in advance. The problem that occurs is the customer in default, then the way to do is to be consulted first and last resort is to auction collateral for a collective agreement that has been done at the beginning of the credit agreement.Key Words : Credit – Collateral – Mortgage right